Development of High-Yielding and Stable Maize (Zea Mays L.) Hybrids Tolerant To Low Soil Nitrogen - Boateng, P.A. (University of Ghana, 2015)
Maize is Ghana’s most important cereal crop and is grown by the vast majority of rural households. It is widely consumed throughout the country, and is the second most important staple food in Ghana, after cassava. Low soil nitrogen (N) impedes maize production in the small-scale farming sector in Ghana. Development of improved maize varieties that are tolerant to low soil N will reduce the need for nitrogen inputs and enhance production. The objectives of this study were to (1) assess maize production constraints of Ghanaian maize farmers, and their perceptions and knowledge on soil fertility, (2) determine heterotic groups and combining ability of grain yield for intermediate maturing maize inbred lines under low and high soil N environments, (3) determine the mode of gene action conditioning grain yield under low N, (4) evaluate the testcrosses (single cross hybrids) for high yield, stability and tolerance to low and high soil N and (5) identify and map Quantitative Trait Loci (QTL) for grain yield (GY) and secondary traits under high N and low soil N. A Participatory Rural Appraisal (PRA) was conducted among 120 farmers in six communities in the forest savanna transition agro-ecological zone of Ghana using Focus Group Discussion (FGD) and semi-structured interview. Thirty-two inbreds received from Institute of Agricultural Research for Development (IRAD), International Institute of Tropical Agriculture (IITA) and International Maize and Wheat Improvement Center (CIMMYT) were crossed to three elite testers (87036, 1368 and 9071) in a line x tester scheme to generate 96 F1 hybrids. The 96 F1 hybrids along with 4 checks were evaluated under low N (30 kg ha-1) and high N(90 kg ha-1 N) soil environments at three locations in Ghana in 2013 and 2014. One hundred and fifty BC2F1 families in a mapping population (CML 444 x CML 494) were used to identify SNP markers associated with quantitative trait loci (QTLs) for yield and yield related traits under low N and high N environments. The PRA revealed low soil fertility, drought, pests and diseases as the major maize production constraints. Most farmers grow improved varieties but, have very little knowledge about hybrids. Farmers preferred low N and drought tolerant varieties with good storability that are disease and insect resistant and require low inputs. They also indicated preference for slender cobs, light in weight with lots of grains. Evaluation of hybrids and inbreds showed genetic variability for grain yield and secondary traits. Significant GCA and SCA effects for grain yield and most measured traits were detected with predominance of GCA effects over SCA effects, indicating that most traits were controlled predominantly by additive gene action. Hybrids CLWN 247 x 9071, ZM523B-29-2-1-1-B*6 x 9071, TZD II 68 x 1368, and P43SCRq Fs100-1-1-8 x 9071 were identified as high yielding, and low N tolerant. These are recommended for further testing for potential release to farmers in low soil N environments. Seven hybrids (CZL 00001 x 9071, LapostaseqC7-F18-3-2-1 x 9071, CLWN 364 x 9071, CLWN 247 x 9071, CLWN 247 X 87036, TZD II 68 x 1368, and CML 395/CML 444 x 9071) were among the 20 best yielding hybrids across environments. These are candidates for further testing for commercialization. Based on SCA of grain yield, HGCAMT and HSGCA methods for heterotic classification, the lines were classified into three heterotic groups for each environment. The inbreds in each heterotic group may be recombined to form populations which could be improved through recurrent selection. Subsequently, inbred lines could be extracted from each population for the production of superior hybrids and synthetics by selfing and crossing onto an inbred tester of opposing heterotic group. The GGE biplot analysis revealed CML 395/ CML 444 x 9071 and TZDII 68 x 1368 as the most high yielding and stable hybrids. These hybrids should also be further tested in multi-location trials and promoted for release. A total of 13 QTLs were identified with 158 SNP markers for six different traits (grain yield, days to silking, stay green characteristic, ears per plant, anthesis silking interval and plant height) under low N environment (9 QTLs) and high N environment (4 QTLs). Five QTLs (qgy-1, qts-1, qsg-1, qsg-4 and qasi-6) for GY, DTS, SG, ASI and EPP, respectively, were close to their adjacent markers, with an interval of 0.7 to 5.2 cM between them and explained phenotypic variance of 9% to 21%.
Thesis(PhD)- University of Ghana, 2015
Keywords: Maize; High-Yieldin; Hybrid; Hybrid